Implementation of Change Management in the GEMARI Program (Healthy Friday and Love for the Nation Movement) at SDN Babatan 1 Surabaya - Alfira Okta Mayangsari; Mohammad Syahidul Haq; Erny Roesminingsih (Journal of Educational Sciences, 2026)
Most elementary schools in Indonesia carry out routine Friday activities without a structured change framework, which makes the educational impact of such programs difficult to measure. Previous research on school change management has focused largely on macro policy reform and has paid limited attention to how participatory change models operate within routine habituation programs. This study addresses that gap by examining the implementation of change management in the GEMARI Program (Gerakan Jumat Sehat dan Cinta Tanah Air) at SDN Babatan 1 Surabaya. The study uses a descriptive qualitative approach with a single case study design. Data were collected through observation, in depth interviews with eight informants including the principal, teachers, and a school committee representative, and documentation. Data validity was tested through source triangulation, member checking, and peer debriefing, then analyzed using the Miles and Huberman interactive model. The findings show that change management was conducted through systematic planning, implementation of four activity pillars based on Kurt Lewin’s unfreeze, change, and refreeze stages, periodic evaluation, and a structured action plan. The novelty of the study lies in an Integrated Participatory Model that combines feasibility analysis, stakeholder engagement, and Lewin’s three stages within a single elementary school habituation program.